THE PRINCIPLE OF GOOD FAITH IN COLLECTIVE WORKING AGREEMENTS BETWEEN EMPLOYERS AND WORKER UNIONS REVIEWED FROM AGREEMENT LAW - Safrida, Safrida; Kamello, Tan; Purba, Hasim; Sembiring, Rosnidar (Inspiring Law Journal, 2024)
The principle of good faith is an important principle in contract law and is accepted in various legal systems, but until now the doctrine of good faith is still controversial. Good faith is known as 2 (two) phases, namely the pre-contract phase and the contract implementation phase. The pre-contract phase is called subjective good faith, which means good faith is more directed towards honesty, while good faith in the contract implementation phase is called objective good faith, which means good faith is interpreted as appropriateness and propriety or fairness. A work agreement is an agreement between a worker/laborer and an entrepreneur or employer which contains work conditions, rights and obligations for the parties. The definition of work conditions is the rights and obligations of employers and workers that have not been regulated in statutory regulations. The work agreement made must not conflict with existing labor agreements or Collective Work Agreements (KKB). This research uses a type of normative legal research sourced from secondary data related to the research topic, secondary data that has been compiled systematically and then analyzed qualitatively. From the research conducted, it was found that the position of the principle of good faith is very important not only at the contract creation (signing) stage and post-contract creation (implementation) stage, but also must exist at the pre-contract creation (drafting) stage because in contract law practice judges use their authority to interfere with the contents of the contract. The legal consequence of a collective work agreement that does not contain the principle of good faith is that if the subjective requirements relating to the subject of the PKB are incomplete, or in other words the conditions that must be fulfilled are not appropriate for those who want to make a PKB, then the PKB that has been made can be requested for cancellation by the trade union/labour union. If the cancellation is not requested by both parties concerned, then the CLA remains valid for the parties. The first legal effort was carried out by PT. United Rope with workers/labor unions is by deliberation to reach a consensus first, although in resolving disputes if there is no good faith in the collective work agreement, it is through 2 (two) systems, namely first, non-litigation/outside the industrial relations court, namely resolution by means of bipartite, mediation, conciliation and arbitration, while the second solution is litigation